2016
DOI: 10.1159/000448217
|View full text |Cite
|
Sign up to set email alerts
|

HLA and Delayed Drug-Induced Hypersensitivity

Abstract: Delayed drug allergy reactions (DDAR) are potentially fatal. Certain human leukocyte antigen (HLA) alleles have been associated with delayed allergy reactions following the administration of particular drugs. Examples are HLA-B*57:01 (abacavir), HLA-B*15:02/HLA-A*31:01 (carbamazepine), and HLA-B*58:01 (allopurinol). Based on the identification of these associations, it may now be possible to prevent certain allergy reactions that were, until recently, considered unpredictable. In this review, we will focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 150 publications
0
30
0
Order By: Relevance
“…This evidence indicated that an immune‐mediated idiosyncratic hepatotoxicity was induced by PM. Delayed adverse drug reactions are driven by the inappropriate activation of T cells . The HLA molecules encoded in the MHC region on chromosome 6 are thought to primarily be key proteins that activate T cells .…”
Section: Discussionmentioning
confidence: 99%
“…This evidence indicated that an immune‐mediated idiosyncratic hepatotoxicity was induced by PM. Delayed adverse drug reactions are driven by the inappropriate activation of T cells . The HLA molecules encoded in the MHC region on chromosome 6 are thought to primarily be key proteins that activate T cells .…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for the number of drug packages sold, we also found a high rate of hospitalisations associated with adverse reactions to antineoplastic and immunosuppressive drugs, supporting some underlying immune deregulation associated with malignancies or autoimmune diseases [ 14 ]. While many cases of EM and SCARs have been reported following the use of several of these drugs, the underlying immunological mechanisms are still only partially identified [ 20 , 39 , 40 ]. Some antineoplastic drugs (e.g., EGFR tyrosine kinase inhibitors) interfere with keratinocyte proliferation, differentiation, and migration, and, thus, might facilitate the development of more severe SCARs.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the frequency of comorbidities potentially associated with an increased risk of SJS/TEN (whether directly or indirectly), namely chronic kidney disease, hypertension, heart failure, diabetes, HIV infection, and liver disease (Additional file 1 : Table S1). Chronic kidney disease is associated with an increased risk of allopurinol-induced SJS/TEN [ 20 ]. As the use of diuretics is also associated with the latter condition [ 21 ], we also assessed conditions whose treatment frequently requires the use of diuretics, namely hypertension, heart failure, and diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…The allele and its tag-SNP were also associated with lower lymphocyte levels and overlapped with T cell regulatory annotations, which suggests that the variant may predispose to a T-cell-mediated, delayed type of penicillin allergy. MHC I molecules are expressed by almost all cells and present peptides to cytotoxic CD8+ T cells, whereas MHC II molecules are expressed by antigen-presenting cells to present peptides to CD4+ T helper lymphocytes 31,34 There are several examples of MHC I alleles associated with drug-induced hypersensitivity mediated by CD8+ T cells 34,36,37 The involvement of T cells in delayed hypersensitivity reactions has been shown by isolating drug reactive T cell clones 38 , and cytotoxic CD8+ T cells have been shown to be relevant especially in allergic skin reactions 3941 . More than twenty years ago, CD8+ T cells reactive to penicillin were isolated from patients with delayed type of hypersensitivity to penicillin 42 .…”
Section: Discussionmentioning
confidence: 99%